Tracking the Pathways of Education in Malaysia: Roots and Routes - Ong, Puay Liu; Sivapalan, Selvadurai; Badariah, Saibeh; Marsitah, Mohd Radzi; Shazlin, Amir Hamzah; Ong, Puay Hoon (Canadian Center of Science and Education, 2013)
Education and the schooling system in Malaysia are constant agenda in the discourse of nation-building. This is because education is regarded as an important avenue to inculcate national consciousness and social cohesion among the people. This article attempts to track the various school systems in Malaysia, with the purpose to highlight the different routes of educational choices in Malaysia. These different routes have their roots in the education policies formulated through time and the growth of a multi-ethnic population in the country. It is argued that these different routes of educational choices display 'inclusiveness', catering to the needs of the diverse population of Malaysia - ethnic, language, religion, regional, disability, vocation, public or private. The Malaysian education scenario represents a complexity of choices, each colouring the pathways of educational experience, expertise and engagement. The guiding question is to what extent this complexity of educational routes influence social cohesion?.